HUBUNGAN PENGGUNAAN MEDIA SOSIAL DENGAN QUARTER LIFE CRISIS PADA MAHASISWA GEN-Z DI UNIVERSITAS TRIBHUWANA TUNGGADEWI - Kipply, Ziu; Rahayu Hastutiningtyas, Wahidyanti; Trishinta, Sirli Mardianna (ASSYIFA : Jurnal Ilmu Kesehatan, 2026)
The use of social media with content on achievements, lifestyles, and successes of others on social media gives rise to a tendency to make social comparisons that cause psychological stress, insecurity, and uncertainty about the future, and have the potential to affect mental health conditions, especially in Gen-Z who are in the early adulthood phase who are vulnerable to experiencing quarter-life crisis. This study aims to determine the relationship between social media use and quarter-life crisis in Gen-Z students at Tribhuwana Tunggadewi University. The study used a quantitative correlational design with a cross-sectional approach. The population was 1,312 and the sample was 307 students selected using a purposive sampling technique. Data were collected using a questionnaire on social media use and quarter-life crisis that had been tested for validity and reliability. Data analysis was performed using the Spearman rank correlation test. The results showed that most respondents had low social media use and moderate quarter-life crisis. Spearman rank test results indicate a significant relationship between social media use and quarter-life crisis (p = 0.000; r = -0.439), indicating a moderately significant relationship between social media use and quarter-life crisis in Gen-Z students. Higher social media use leads to lower levels of quarter-life crisis. Future research is recommended to examine other factors that may influence quarter-life crisis and employ different research designs to obtain more comprehensive results.